Deconstruction of Penal System Policy on Tax Law in Indonesia against Liability for Corporate Income Tax Evasion - Annika Rahmawati (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The purpose of this study is to simplify legal policies in the Law on General Provisions and Tax Procedures by the values of Pancasila in technical and its implementation in the application of law and law implementation in tax crimes. Normative juridical research methods are processed qualitatively and descriptively, using sources of legal materials" secondary data" "primary" legal materials, and tertiary legal materials, laws, and regulations as rules or norms that become parameters of behavior. legal principles, as well as legal doctrines to answer growing legal issues. Such as the statute approach. Case approach, and conceptual approach. To achieve justice that is manifest in the imposition of criminal sanctions and can be implemented for perpetrators of tax evasion crimes, and focus on criminal purposes so that they can be held criminally accountable for their actions by the punishment given. The provisions in the special criminal law impose sanctions that are more severe than general crimes. At the same time as a consideration to answer the problem of how the deconstruction of the penal system policy on tax law in Indonesia against the criminal liability of corporate income tax evasion can be applied as a reference to make new legal constructions useful for the Indonesian state by deconstructing the diction or phrase of the criminal act of taxation and, technical management and separation of powers.